Association between developmental dental anomalies, early childhood caries and oral hygiene status of 3-5-year-old children in Ile-Ife, Nigeria - Morenike Oluwatoyin Folayan; Michael Alade; Abiola Adeniyi; Maha El Tantawi; Tracy L. Finlayson (BMC, 2019)
Abstract Background To determine the association between developmental dental anomalies (DDA), early childhood caries (ECC) and oral hygiene status of 3-5-year-old children resident in Ile-Ife, Nigeria. Methods This was a cross-sectional study. We analyzed data for 3-5-year-olds extracted from the dataset of a household survey collected to determine the association between ECC and maternal psychosocial wellbeing in children 0-5-year-old. The outcome variables for the study were ECC and poor oral hygiene. The explanatory variable was the presence of developmental dental anomalies (supernumerary, supplemental, mesiodens, hypodontia, macrodontia, microdontia, peg-shaped lateral, dens evaginatus, dens invaginatus, talons cusp, fusion/germination, hypoplasia, hypomineralized second molar, fluorosis, amelogenesis imperfecta). The prevalence of each anomaly was determined. Poisson regression analysis was conducted to determine the association between presence of developmental dental anomalies, ECC and oral hygiene status. The model was adjusted for sex, age and socioeconomic status. Results Of the 918 children examined, 75 (8.2%) had developmental dental anomalies, 43 (4.7%) had ECC, and 38 (4.1%) had poor oral hygiene. The most prevalent developmental dental anomalies was enamel hypoplasia (3.9%). Of the 43 children with ECC, 6 (14.0%) had enamel hypoplasia and 3 (7.6%) had hypomineralized second primary molar. There was a significant association between ECC and enamel hypoplasia (p < 0.001) and a borderline association between ECC and hypomineralized second primary molars (p = 0.05). The proportion of children with poor oral hygiene (PR: 2.03; 95% CI: 0.91-4.56; p = 0.09) and ECC (PR: 2.02; 95% CI: 0.92-4.46; p = 0.08) who had developmental dental anomalies was twice that of children with good oral hygiene and without ECC respectively, although the differences did not reach statistical significance. Conclusions Enamel hypoplasia and hypomineralized second primary molars are developmental dental anomalies associated with ECC. developmental dental anomalies also increases the probability of having poor oral hygiene in the population studied.